Oral Treprostinil for the Treatment of Pulmonary Arterial Hypertension in Patients Transitioned from Parenteral or Inhaled Prostacyclins: Case Series and Treatment Protocol. (1st March 2016) - Coons, James C.; Miller, Taylor; Simon, Marc A.; Ishizawar, David C.; Mathier, Michael A.
Abstract : Oral treprostinil (TRE) is a prostacylin approved for the management of pulmonary arterial hypertension (PAH). Few data exist to guide the use of oral TRE as a replacement for parenteral or inhaled prostacyclins. Therefore, the purpose of this report was to describe our experience with oral TRE to transition patients from parenteral or inhaled TRE. We describe a case series of patients admitted for a 4‐day hospital stay to transition from parenteral or inhaled TRE. Appropriate criteria for transition included stable patients with improved symptoms/functional capacity, patients who could not tolerate intravenous prostacyclin due to infection or subcutaneous prostacyclin due to pain, and patient preference for transition. The dosing protocol for transition is described. A total of 9 patients generally representative of a typical PAH demographic and background medical therapy were included. Patients were initiated at either 0.5 or 1 mg 3 times daily and discharged on a median dose of 8 mg 3 times daily. Our protocol resulted in 6 of 9 patients who successfully transitioned at a median follow‐up of 47 weeks. Two patients had to return to their previous prostacyclin therapy based on the presence of clinical worsening and adverse events ( n = 1) and adverse events alone ( n = 1). Another patient discontinued therapy due to plans for hospice care. Oral TRE may serve an important role in prostacyclin transitions in carefully selected, stable patients who receive background oral therapy for PAH.